PO11 Metabolomic Characterization of Miconia (Ruiz & Pav.) Species Using UHPLC-HRMS and Feature-based Molecular Networking - Celis Celis, Erika Mayerly; Lobo-Echeverri, Tatiana (Revista Productos Naturales, 2025)
Metabolomic Profiling of Miconia Species by UHPLC-HRMS
Keywords: Andean plant species, metabolomics, Miconia spp., molecular networking, natural products